What Can Postural Yoga Contribute to an Embodied Christian Spirituality? An Analysis of the Strengths and Weaknesses of Postural Yoga in the Light of Kashmir Śivaism - Fabrice Blée (Religions, 2022)
In this article, I propose to examine how the practice of āsanas (postural yoga) offered in Western yoga studios might contribute to an embodied Christian spirituality. I will do this with reference to Kashmir Śivaism, which links postural yoga to the “way of action” (kriyopāya) and considers it to be ‘inferior’ to the two other paths to supreme liberation, that of energy (śāktopāya) and that of will (śāmbhavopāya). In my critique of the widespread contemporary emphasis on postutral yoga, I will point out both its strengths and its weaknesses, and reaffirm the role of the body in our relationship with God.